THE SUFI ORDER AND PHILANTHROPY:A CASE STUDY OF PHILANTROPHICAL ACTIVISM OF THE NAQSYABANDIYAH AL-HAQQANI SUFI ORDER IN INDONESIA - Sakhok, Jazilus; Munandar, Siswoyo Aris (Teosofia: Indonesian Journal of Islamic Mysticism, 2019)
This study is entitled "Tarekat and Philanthropy: Study of the Social Activities of the Al-Haqqani Naqsyabandiyah Congregation in Indonesia". The background of this case study is Sufism so far known as the esoteric dimension in Islam. This identification often gets Sufism considered to be mystical and ascetic. So far, the Sufis are seen as a group of people who emphasize individual piety (personal) rather than social piety. However, in contrast to the Naqshbandiyah Al-Haqqani Congregation, its students must go into the community and be active in social life. In terms of the formulation of the problem two questions can be drawn namely; First, what is behind the Naqshabandiyah Al-Haqqani Congregation is engaged in social and philanthropic activities. Second, What is the social activity and philanthropy of the Al-Haqqani Naqshbandiyah Order. Efforts to answer the problems in this study will be used field research methods, namely by digging field data and observing directly. This paper describes the social activities of the tarekat as the object of study. The results of this study indicate that there is a Naqsyabandiyah Al-Haqqani order which is active in social and philanthropy. The social activities of the Al-Haqqani Naqsyabandiyah Congregation are realized through institutions such as: HCNS (Hajjah Naziha Charitable Society), Rumi CafÃ©, Karem Food Drive, Rabbani Sufi Center and CV Sogan Jaya / Sogan Batik.